The end of a professional sport career: Ensuring a positive transition - Knights, S.; Sherry, E.; Ruddock-Hudson, M.; O`Halloran, P. (Journal of Sport Management, 2019)
The purpose of this research was to explore the experience of transition and life after sport in a group of retired professional athletes. A total of 45 retired athletes from three national football leagues took part in semistructured interviews. Two overarching themes emerged from the data analysis: (a) preparing for transition and planning for retirement and (b) supportive environment. For athletes in this study, four main factors were identified as critical to promoting a positive transition. The nature of the transition also directly affected athletes` experience of retirement from sport and, thus, their experience of flourishing in life after sport. The majority of participants in this study indicated that they lacked support from their sporting club and governing bodies both during their transition and in retirement. Planning for retirement and preparing for the future positively affected their ability to flourish in retirement. Recommendations for sport managers and athlete support services are provided.